CHECKLIST OF CHIRONOMIDAE (INSECTA: DIPTERA) FROM URUGUAY - Castro, Manuel; Canneva, Bruno; Martínez, María; Arocena, Rafael (Zootaxa, 2024)
This study presents a comprehensive list of Chironomidae species recorded in Uruguay, compiled through a bibliographic review. A total of 41 genera of Chironomidae are documented, categorized into four subfamilies: Chironominae, Diamesinae, Orthocladiinae, and Tanypodinae. Additionally, genera lacking named species are included in the list, identified primarily through the analysis of larval characteristics, particularly from limnological investigations.